Bending-resistant transparent polyamide-imide film as well as preparation method and application thereof

By introducing LiCl and alkaline earth metal ions into the transparent polyimide film, the cross-linking network is constructed, and the film has poor resistance during bending and folding is solved, and high bending resistance and excellent flexibility and light transmission are achieved.

CN119638995AActive Publication Date: 2025-03-18SICHUAN AONIU NEW MATERIAL CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411817127.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing transparent polyimide films have poor resistance during bending and folding, and are prone to plastic slips and wrinkles, which affect the reliability of flexible electronic devices.

Method used

By introducing monovalent alkali metal salt LiCl and polyvalent alkaline earth metal ions Ca2+ or Mg2+, a non-covalent crosslinking network of monovalent/multivalent ion coordination is constructed to enhance the force and entropy elasticity between the molecular chains and prevent the plastic slip of the macromolecular chains in cyclic folding.

Benefits of technology

It realizes high bending resistance of transparent polyamide-imide film, and can be bent 200,000 times under a bending radius of 0.5mm and continuously crack, and has excellent flexibility and high light transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638995A_ABST
    Figure CN119638995A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flexible display materials, and discloses a bending-resistant transparent polyamide-imide film as well as a preparation method and application thereof. The preparation method comprises the following steps: dissolving a dianhydride monomer in a diamine solution for polymerization reaction to obtain a polyamide acid solution; adding a monovalent alkali metal salt and an acyl chloride monomer into the polyamide acid solution, and copolymerizing to obtain a precursor solution; adding a dehydrating agent and a catalyst into the precursor solution, carrying out dehydration imidization to obtain a polyamide-imide solution, and mixing the polyamide-imide solution with a precipitator for precipitation to obtain a polyamide-imide solid; the preparation method comprises the following steps: dissolving a polyamide-imide solid in a polar organic solvent, adding multivalent alkaline earth metal salt to obtain a multi-coordinated polyamide-imide solution, coating the surface of a substrate with the multi-coordinated polyamide-imide solution, heating, curing, and demolding to obtain the composite material. The highest tensile strength of the transparent polyamide-imide film prepared by the invention is 160MPa, and the transmittance at the wavelength of 550nm is gt; 88%, and the yellowness value is lt; and 3, the cable can be bent for 200,000 times under the condition that the bending radius is 0.5 mm, and cannot be broken.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of flexible display materials, and in particular to a bending-resistant transparent polyamide-imide film and a preparation method and application thereof. Background Art

[0002] With the rapid development of flexible electronic devices, the market demand for bendable, foldable and wearable display devices continues to grow. Traditional brittle glass is difficult to meet the needs of flexible display devices, and the flexible cover film prepared by combining polymer film with transparent protective coating can effectively solve the problems faced by flexible display devices and replace traditional brittle glass.

[0003] The flexible polymer film and protective coating used to prepare the flexible cover film must meet the following key requirements: 1) excellent optical transparency (should be comparable to inorganic glass); 2) high tensile strength and modulus; 3) good heat resistance (high glass transition temperature Tg) and excellent dimensional stability (low coefficient of thermal expansion CTE); 4) excellent ductility and excellent folding reliability (able to withstand more than 200,000 folding cycles); 5) easy processing and large-scale production. Transparent polyimide (CPI) film has become the most promising candidate material for cover films of flexible display devices due to its excellent optical transparency, excellent mechanical properties, high thermal stability and good chemical resistance.

[0004] However, the conformational entropy or entanglement of CPI is very small, and the limited entropy elasticity and deformation space cannot withstand the molecular chain slippage caused by the long-term folding of the film, resulting in its poor bending resistance. The accumulation of plastic deformation leads to the formation of visible wrinkles, affecting the reliability of flexible electronic devices.

[0005] Building a cross-linked structure in the film is considered to be an effective means to prevent the plastic slip of the macromolecular chain during cyclic bending, thereby avoiding the early formation of creases. Based on this, the present application develops a transparent polyamide-imide film with high bending resistance, thereby improving the reliability of flexible electronics. Summary of the invention

[0006] The present application provides a bending-resistant transparent polyamide-imide film and a preparation method and application thereof, aiming to solve the problem of poor bending resistance of existing transparent polyimide films.

[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0008] In a first aspect of the present application, a method for preparing a bending-resistant transparent polyamide-imide film is provided, comprising:

[0009] S1, in an inert atmosphere, dissolving a diamine monomer in a polar organic solvent to obtain a diamine solution; dissolving a dianhydride monomer in the diamine solution to carry out a polymerization reaction to obtain a polyamic acid solution;

[0010] S2, adding a monovalent alkali metal salt to the polyamic acid solution, and then adding an acyl chloride monomer to carry out a copolymerization reaction to obtain a precursor solution;

[0011] S3, adding a dehydrating agent and a catalyst to the precursor solution to perform dehydration imidization to obtain a polyamide-imide solution; mixing the polyamide-imide solution with a precipitating agent to perform precipitation to obtain a polyamide-imide solid containing a monovalent alkali metal salt;

[0012] S4, dissolving the polyamide-imide solid containing a monovalent alkali metal salt in a polar organic solvent, then adding a multivalent alkaline earth metal salt, and stirring evenly; filtering and degassing to obtain a multi-coordinated polyamide-imide solution;

[0013] S5, coating the multi-coordinated polyamide-imide solution on the surface of the substrate, and curing it by heating to obtain a bend-resistant transparent polyamide-imide film.

[0014] Preferably, the diamine monomer includes at least one of the following compounds 1-1a to 1-15a:

[0015]

[0016] Preferably, the dianhydride monomer includes at least one of the compounds shown in 1-1b to 1-12b:

[0017]

[0018] Preferably, the acyl chloride monomer includes at least one of the compounds shown in 1-1c to 1-18c:

[0019]

[0020] Preferably, the polar organic solvent comprises at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc);

[0021] The dehydrating agent is acetic anhydride;

[0022] The catalyst is pyridine, triethylamine or isoquinoline;

[0023] The precipitant is deionized water, ethanol or a mixture of deionized water and ethanol.

[0024] Preferably, the ratio of the molar number of the diamine monomer to the total molar number of the dianhydride monomer and the acyl chloride monomer is 1:(1-1.03); wherein the molar ratio of the dianhydride monomer to the acyl chloride monomer is 9:1-1:9;

[0025] The molar ratio of the dehydrating agent to the dianhydride monomer is (2-2.5):1;

[0026] The molar ratio of the dehydrating agent to the catalyst is 1:(0.5-2).

[0027] Preferably, the monovalent alkali metal salt is LiCl; the amount of the monovalent alkali metal salt added is 0.5 to 2.0 wt % of the sum of the amounts of the diamine monomer and the dianhydride monomer;

[0028] The multivalent alkaline earth metal salt comprises at least one of CaCO3, CaF2, CaSO4, CaCl2, MgCO3, MgF2, MgSO4 or MgCl2;

[0029] The added amount of the multivalent alkaline earth metal salt is 0.5-10 wt % of the solid mass of the polyamide-imide containing the monovalent alkali metal salt.

[0030] Preferably, the temperature of the dehydration imidization in step S3 is 20 to 60° C. and the time is 1 to 24 hours;

[0031] The precipitation temperature is 10-40°C.

[0032] The second aspect of the present application provides a bending-resistant transparent polyamide-imide film prepared by the above preparation method.

[0033] The third aspect of the present application provides application of the above-mentioned bending-resistant transparent polyamide-imide film in a flexible display device.

[0034] Compared with the prior art, the beneficial effects of this application are:

[0035] The preparation method of the present application controls the viscosity of the polymerization system after the polyamic acid and the amide bond are introduced by introducing a monovalent alkali metal salt LiCl, and acts on the amide bond in the solution phase to reduce the intermolecular force, which mainly plays a solubilizing role in the early stage, improves the solubility of the polyamic acid-polyamide copolymer, thereby improving the casting film-forming performance of the polymer glue, and at the same time participates in the multi-coordination synergistic effect of the film after curing and forming; the introduction of the amide structure helps to effectively stack and orient the chains, and can effectively improve the mechanical properties of the film; the introduction of the multivalent colorless alkaline earth metal ion Ca 2+ or / and Mg 2+It forms a multi-coordinate structure with the amide bond, and forms a cation-π interaction with the benzene ring and the imide ring. The present application constructs a monovalent / multivalent ion coordination non-covalent cross-linked network through the synergistic effect of the above strategies, enhances the interaction force and entropy elasticity between molecular chains to prevent the plastic slip of the macromolecular chain in the cyclic folding, and then obtains a bend-resistant transparent polyamide-imide film with an energy dissipation mechanism, which has excellent flexibility and high light transmittance.

[0036] The non-biaxially stretched transparent polyamide-imide film with a multi-coordination structure prepared in the present application has a tensile strength of up to 160 MPa, a transmittance of >88% at a wavelength of 550 nm, a yellowness value of <3, and can be bent 200,000 times at a bending radius of 0.5 mm without breaking. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0038] Figure 1 The physical picture and SEM spectrum of the transparent polyamide-imide film prepared in Example 1;

[0039] Figure 2 The infrared spectra of the transparent polyamide-imide films prepared in Examples 1-3 and Comparative Example 1;

[0040] Figure 3 The SEM spectra of the transparent polyamide-imide films prepared in Examples 1-3 and Comparative Example 1 after bending. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0043] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0044] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0045] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0046] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0047] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0048] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0049] In a first aspect, the present application provides a method for preparing a bending-resistant transparent polyamide-imide film, comprising:

[0050] S1, in an inert atmosphere, dissolving a diamine monomer in a polar organic solvent to obtain a diamine solution; dissolving a dianhydride monomer in the diamine solution to carry out a polymerization reaction to obtain a polyamic acid solution;

[0051] In the present application, the diamine monomer has a non-planar or strong electronegativity, and includes at least one of the following compounds 1-1a to 1-15a:

[0052]

[0053] In the present application, the polar organic solvent is used to dissolve the diamine monomer, and the polar organic solvent includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc), preferably N,N-dimethylacetamide.

[0054] In the present application, the dianhydride monomer includes at least one of the compounds shown in 1-1b to 1-12b:

[0055]

[0056] In the present application, the diamine monomer is preferably 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB); the dianhydride monomer is preferably 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA) and / or 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA).

[0057] In the present application, the polymerization reaction temperature is preferably room temperature, and the reaction time is preferably 3 to 6 hours; the polymerization reaction is preferably carried out under stirring, and the stirring speed is preferably 350 to 500 rpm.

[0058] S2, adding a monovalent alkali metal salt to the polyamic acid solution, and then adding an acyl chloride monomer to carry out a copolymerization reaction to obtain a precursor solution;

[0059] In the present application, the acyl chloride monomer includes at least one of the following compounds:

[0060]

[0061] The acyl chloride monomer is preferably terephthaloyl chloride (TPC), isophthaloyl chloride (IPC) and / or 4,4'-biphenyl dicarboxylic acid chloride (BPDC). In the present application, the temperature for adding the acyl chloride monomer is preferably room temperature or in an ice bath. After adding the acyl chloride monomer, the solid content of the obtained mixed solution is preferably 5 to 20 wt%, more preferably 10 to 15 wt%.

[0062] In the process of constructing a polyamic acid (PAA)-based polymer film, the coordination between ions and carboxylic acid groups can effectively increase the viscosity of the polyamic acid. In the present application, a monovalent alkali metal salt LiCl is selected as a solubilizing ion, and the monovalent coordination can effectively reduce hydrogen bond interactions and significantly improve the viscosity of the polymer. In the present application, LiCl solid or LiCl solution can be added to the polyamic acid solution, wherein the amount of LiCl added is 0.5 to 2.0 wt% of the sum of the amounts of the diamine monomer and the dianhydride monomer, preferably 0.8 wt%.

[0063] In the present application, the copolymerization reaction is preferably carried out at room temperature or in an ice bath, and the reaction time is preferably 12 to 24 hours; the copolymerization reaction is preferably carried out under stirring conditions; and the stirring speed is preferably 200 to 350 rpm.

[0064] In the present application, the ratio of the molar number of the diamine monomer to the total molar number of the dianhydride monomer and the acyl chloride monomer is preferably 1:(1-1.03); wherein the molar ratio of the dianhydride monomer to the acyl chloride monomer is 9:1-1:9.

[0065] S3, adding a dehydrating agent and a catalyst to the precursor solution to perform dehydration imidization to obtain a polyamide-imide solution; mixing the polyamide-imide solution with a precipitating agent to perform precipitation to obtain a polyamide-imide solid containing a monovalent alkali metal salt;

[0066] In the present application, the dehydrating agent is acetic anhydride; the catalyst is pyridine, triethylamine or isoquinoline, preferably pyridine. The molar ratio of the dehydrating agent to the dianhydride monomer is (2-2.5):1; the molar ratio of the dehydrating agent to the catalyst is 1:(0.5-2).

[0067] In the present application, the temperature of the dehydration imidization is preferably 20-60°C, and the time is 1-24h; the precipitant is deionized water, ethanol or a mixture of deionized water and ethanol, wherein the volume ratio of water to ethanol in the mixture is preferably 1:1; the temperature of the precipitation is preferably 10-40°C, more preferably 25°C, and washing is preferably performed after precipitation.

[0068] S4, dissolving the polyamide-imide solid containing a monovalent alkali metal salt in a polar organic solvent at room temperature, then adding a multivalent alkaline earth metal salt, and stirring evenly; filtering and degassing to obtain a multi-coordinated polyamide-imide solution;

[0069] In the present application, the multivalent alkaline earth metal salt includes at least one of CaCO3, CaF2, CaSO4, CaCl2, MgCO3, MgF2, MgSO4 or MgCl2, preferably CaCl2, MgCl2 or a mixture of CaCl2 and MgCl2. Wherein, the addition amount of the multivalent alkaline earth metal salt is 0.5-10wt% of the solid mass of the polyamide-imide containing the monovalent alkali metal salt, preferably 1wt%.

[0070] In the present application, the stirring time is preferably 6 to 12 hours, and the stirring speed is preferably 150 to 250 rpm.

[0071] The present application does not have any special restrictions on the operation of filtering and degassing, and the technical solutions of filtering and degassing well known to those skilled in the art can be used. In the embodiments of the present application, the filtration is preferably performed by a syringe filter or a sand core filter; the degassing temperature is preferably room temperature, and the degassing method is preferably vacuum degassing or static degassing.

[0072] In the present application, the solid content of the obtained multi-coordinated polyamide-imide solution is preferably 5 to 20%, and more preferably 10 to 15%.

[0073] S5, coating the multi-coordinated polyamide-imide solution on the surface of the substrate, curing it by heating, and then demoulding it to obtain a bend-resistant transparent polyamide-imide film. The substrate is preferably a glass bottom plate.

[0074] The present invention is firstly heat-insulated at 50-80°C for 1-3h, then heat-insulated at 150-180°C for 1-3h, and finally heat-insulated at 320-350°C for 1-2h, and the solvent is evaporated for curing, and then demoulding is performed in deionized water.

[0075] This application enhances the hydrogen bonding effect in the transparent polyimide CPI molecular chain by introducing an amide structure, which can effectively promote the stacking and orientation of the chain, thereby significantly improving the mechanical properties of the CPI film. At the same time, since the amide bond has a resonance structure, when it is combined with an aromatic group, the electronic transition (such as n-π* transition) is constrained by symmetry, which has advantages in maintaining the absorption characteristics of molecular coplanarity, thereby effectively reducing light absorption and improving the light transmittance of the material. Therefore, the amide bond in the constructed polyamide-imide (CPAI) hardly absorbs visible light and can significantly improve the rigidity of the polymer chain.

[0076] The present application regulates the viscosity of polymer by the coordination of monovalent alkali metal salt, and can significantly improve the cast film-forming performance of polymer glue. In the construction process of polyamic acid (PAA) based polymer film, the coordination between ion and carboxylic acid group can effectively improve the viscosity of polyamic acid. With the advancement of chemical imidization reaction, the coordination ability of imide ring is significantly weakened, and in the formation process of polyimide, ion does not participate in the reaction. In the stage of introducing amide bond, strong hydrogen bonding between molecules may cause the gel precipitation of polymerization system. Therefore, using ions coordinated with amide group, especially ions that can form coordination with carbon atoms of specific groups, can effectively weaken the interaction between molecules, so as to play a solubilizing effect. Among various ions, monovalent alkali metal salts (such as LiCl) with weak coordination ability are used as effective solubilizing ions, and hydrogen bonding interactions can be effectively reduced and the viscosity of polymer can be significantly improved by monovalent coordination. And multivalent alkaline earth metal ions usually have strong coordination ability, which can cause the increase of polymer viscosity, thereby adversely affecting polymerization. However, multivalent alkaline earth metal ions usually have strong coordination ability, which will lead to an increase in polymer viscosity and thus have an adverse effect on the polymerization reaction.

[0077] Specifically, the present application introduces a monovalent alkali metal salt LiCl to adjust the viscosity of the polymer after the polymerization of polyamic acid is completed, and then adds acyl chloride for copolymerization to generate a polyamide-polyamic acid copolymer. In the solution phase, LiCl as a monovalent salt can act with the amide bond through a single coordination effect to reduce the intermolecular force, improve the solubility of the polyamic acid-polyamide copolymer, thereby improving the casting film-forming performance of the polymer glue and playing a solubilizing role. Subsequently, by maintaining a low temperature environment for the polymer during precipitation and washing, LiCl is retained in the polyamide-imide polymer solid; Li in the solid film + It is transformed into a coordination effect with the amide bond, participating in the reaction of alkaline earth metal ions (such as Ca 2+ Mg 2+ ) to form Li + , Ca 2+ and / or Mg 2+ The network structure significantly enhances the mechanical properties, heat resistance and thermal dimensional stability of the film, and reduces the electron transfer recombination effect between macromolecular chains, thereby improving the light transmittance of the film. + , Ca 2+ and Mg 2+ The concentration and ratio of polyamide-imide film can be further adjusted to meet the specific needs of different application scenarios.

[0078] This application prevents the plastic slip of macromolecular chains during cyclic bending by constructing a cross-linked structure in the film, thereby avoiding the formation of early creases. Based on the presence of functional amide bonds, colorless alkaline earth metal ions are introduced to coordinate with amide bonds to form a non-covalent cross-linked network, which can work together with the hydrogen bond network to form a quasi-cross-linked network, effectively dissipating the energy generated by the molecular chain during the bending process. At the same time, the benzene ring or imide ring can form a cation-π interaction with the alkaline earth metal cation. This effect is different from the electron sharing and orbital overlap in the coordination bond, and has the characteristics of colorless transparency, large binding area and adjustable bond angle. In particular, Ca in alkaline earth metals 2+ or Mg 2+ ions, due to their higher valence and multi-coordination ability, make Ca 2+ or Mg 2+ The amount of salt used is more controllable and the cost is relatively low.

[0079] This application constructs a monovalent / multivalent ion coordination non-covalent cross-linked network through the synergistic effect of the above strategies, enhances the interaction force and entropy elasticity between molecular chains to prevent the plastic slip of macromolecular chains during cyclic folding, and thus obtains a bend-resistant transparent polyamide-imide film with an energy dissipation mechanism, which has excellent flexibility and high light transmittance.

[0080] The bending-resistant transparent polyamide-imide film prepared in the present application has a maximum tensile strength of 160MPa, a transmittance of >88% at a wavelength of 550nm, a yellowness value of <3, and can be bent 200,000 times without breaking at a bending radius of 0.5mm. The bending-resistant transparent polyamide-imide film of the present application can be used for flexible display devices.

[0081] The present application is further described below by way of examples.

[0082] Example 1

[0083] This embodiment provides a method for preparing a bending-resistant transparent polyamide-imide film, comprising:

[0084] S1, under nitrogen protection, dissolving 10 mmol of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl TFMB in 60 ml of N,N-dimethylacetamide to obtain a diamine solution; adding 4 mmol of 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride to the diamine solution, mixing and stirring at 400 rpm for 3 h to obtain a polyamic acid solution;

[0085] S2, adding 50 mg of LiCl solid to the polyamic acid solution, mixing and stirring at a speed of 400 rpm for 1 hour, to obtain a Li ion coordinated polyamic acid mixed solution; adding 6 mmol of terephthaloyl chloride TPC to the Li ion coordinated polyamic acid mixed solution, and adding DMAc dropwise to maintain the solid content of the obtained mixed solution after adding TPC at 10wt%, and continuing to stir and react at a speed of 250 rpm at room temperature for 12 hours after the addition is completed, to obtain a polyamide-amic acid (PAA+PA) solution;

[0086] S3, adding 8 mmol of acetic anhydride and 4 mmol of anhydrous pyridine to the polyamide-amic acid solution, reacting at 60° C. for 4 h, and after the reaction, using a mixture of methanol and water (the volume ratio of methanol to water in the mixture is 1:1) as a precipitant for precipitation, and washing the precipitate with deionized water to obtain a white fibrous polyamide-imide resin;

[0087] S4, dissolving 2g of polyamide-imide resin in DMAC, adding CaCl2 powder of 1wt% of the mass of the polyamide-imide resin, mixing and stirring at 200rpm for 6h at room temperature, and then vacuum degassing at room temperature to obtain a 1wt% CaCl2 powder. 2+ A polyamide-imide solution; wherein the solid content of the polyamide-imide solution is 10%;

[0088] S5 The above containing 1wt% Ca 2+ The polyamide-imide solution was evenly coated on a glass bottom plate by a coating machine, and then placed in a vacuum drying oven, first kept at 80°C for 1 hour, then kept at 180°C for 1 hour, and finally kept at 250°C for 1 hour. After cooling to room temperature, it was taken out and placed in deionized water. After the film fell off automatically, it was placed in a vacuum drying oven at 80°C for 2 hours to obtain a transparent polyamide-imide film, recorded as CPAI-1%Ca.

[0089] The chemical structure of the transparent polyamide-imide film prepared in Example 1 is shown below.

[0090]

[0091] Example 2

[0092] The difference between Example 2 and Example 1 is that in step S4, CaCl2 is replaced by MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 2 is denoted as CPAI-1%Mg.

[0093] Example 3

[0094] The difference between Example 3 and Example 1 is that in step S4, 1 wt% of CaCl2 is replaced by 0.5 wt% of CaCl2 and 0.5 wt% of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 3 is denoted as CPAI-1%CaMg.

[0095] Example 4

[0096] The difference between Example 4 and Example 1 is that the amount of CaCl2 in step S4 is changed to 0.5 wt %, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 4 is denoted as CPAI-0.5%Ca.

[0097] Example 5

[0098] The difference between Example 5 and Example 1 is that the amount of CaCl2 in step S4 is changed to 2 wt %, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 5 is denoted as CPAI-2%Ca.

[0099] Example 6

[0100] The difference between Example 6 and Example 1 is that the amount of CaCl2 in step S4 is changed to 5 wt %, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 6 is denoted as CPAI-5%Ca.

[0101] Example 7

[0102] The difference between Example 7 and Example 1 is that the amount of CaCl2 in step S4 is changed to 10 wt %, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 7 is denoted as CPAI-10%Ca.

[0103] Example 8

[0104] The difference between Example 8 and Example 1 is that in step S4, 1 wt % of CaCl2 is replaced by 0.5 wt % of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 8 is denoted as CPAI-0.5%Mg.

[0105] Example 9

[0106] The difference between Example 9 and Example 1 is that in step S4, 1 wt % of CaCl2 is replaced by 2 wt % of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 9 is denoted as CPAI-2%Mg.

[0107] Example 10

[0108] The difference between Example 10 and Example 1 is that in step S4, 1 wt % of CaCl2 is replaced by 5 wt % of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 10 is denoted as CPAI-5%Mg.

[0109] Embodiment 11

[0110] The difference between Example 11 and Example 1 is that in step S4, 1 wt % of CaCl2 is replaced by 10 wt % of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 11 is denoted as CPAI-10%Mg.

[0111] Example 12

[0112] The difference between Example 12 and Example 1 is that in step S4, 1 wt% of CaCl2 is replaced by 0.25 wt% of CaCl2 and 0.25 wt% of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 12 is denoted as CPAI-0.5%CaMg.

[0113] Example 13

[0114] The difference between Example 13 and Example 1 is that in step S4, 1 wt% of CaCl2 is replaced by 1 wt% of CaCl2 and 1 wt% of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 13 is denoted as CPAI-2%CaMg.

[0115] Embodiment 14

[0116] The difference between Example 14 and Example 1 is that in step S4, 1 wt% of CaCl2 is replaced by 2.5 wt% of CaCl2 and 2.5 wt% of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 14 is denoted as CPAI-5%CaMg.

[0117] Embodiment 15

[0118] The difference between Example 15 and Example 1 is that in step S4, 1 wt % of CaCl2 is replaced by 5 wt % of CaCl2 and 5 wt % of MgCl2, and the rest is the same as Example 1. The transparent polyamide-imide film prepared in Example 15 is denoted as CPAI-10%CaMg.

[0119] Comparative Example 1

[0120] The difference between the comparative example and the example 1 is that no multivalent alkaline earth metal salt CaCl2 is added to S4, and the rest is the same as the example 1. The transparent polyamide-imide film prepared in the comparative example 1 is denoted as CPAI.

[0121] The transparent polyamide-imide film prepared in Example 1 is as follows: Figure 1 As shown in a, it is colorless and transparent, and has good bending resistance; its SEM spectrum is as follows Figure 1 As shown in b, no phase separation and crystallization occurred.

[0122] The transparent polyamide-imide films CPAI-1%Ca, CPAI-1%Mg, CPAI-1%CaMg and CPAI prepared in Examples 1-3 and Comparative Example 1 were analyzed by infrared spectroscopy. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the strong absorption peaks caused by the asymmetric and symmetric stretching of the imine C=O group appear at 1786 and 1724 cm -1 The absorption peak caused by the stretching of imine CN appears at 1370 cm -1 In addition, at 1674cm -1 The absorption peak caused by the stretching of the amide group C=O appears at 1662 cm -1 and 1713cm -1 ) completely disappeared, indicating that the CPAI film was completely imidized after heat treatment.

[0123] The optical properties of the transparent polyamide-imide films prepared in Examples 1-15 and Comparative Example 1 were tested, and the test results are shown in Table 1.

[0124] Table 1 Optical properties of transparent polyamide-imide films

[0125]

[0126] As can be seen from Table 1, the optical properties of the polyamide-imide films prepared by introducing alkaline earth metals in Examples 1-15 of the present application are equivalent to those of the polyamide-imide film without alkaline earth metals in Comparative Example 1. The introduction of a small amount of alkaline earth metals can effectively ensure the optical properties of the CPAI film.

[0127] The transparent polyamide-imide films prepared in Examples 1-15 and Comparative Example 1 were tested for mechanical properties. The test results are shown in Table 2.

[0128] Table 2 Mechanical properties data of transparent polyamide-imide film

[0129] Implementation CPAIs Tensile strength / MPa Elastic modulus / GPa Elongation at break / % Comparative Example 1 CPAI 138.2±6.07 4.0±0.11 6.66±0.97 Example 4 CPAI-0.5%Ca 158.22±4.42 5.0±0.15 5.20±0.58 Example 1 CPAI-1%Ca 156.30±7.82 4.62±0.23 7.83±0.38 Example 5 CPAI-2%Ca 160.21±2.87 4.61±0.08 12.88±1.05 Example 6 CPAI-5%Ca 135.18±2.76 3.95±0.04 21.65±4.07 Example 7 CPAI-10%Ca 104.21±3.17 3.08±0.08 25.61±3.24 Example 8 CPAI-0.5%Mg 145.57±1.71 4.23±0.08 8.33±0.53 Example 2 CPAI-1%Mg 155.67±5.30 4.51±0.10 9.53±0.87 Example 9 CPAI-2%Mg 159.76±1.12 4.71±0.03 20.73±3.19 Example 10 CPAI-5%Mg 116.62±5.82 3.39±0.04 34.88±5.44 Embodiment 11 CPAI-10%Mg 81.6±4.83 2.79±0.11 13.90±2.18 Example 12 CPAI-0.5% CaMg 140.32±2.18 4.04±0.07 6.89±0.58 Example 3 CPAI-1% CaMg 152.60±5.12 4.14±0.09 8.11±0.72 Example 13 CPAI-2% CaMg 166.92±4.28 4.54±0.12 15.51±1.07 Embodiment 14 CPAI-5% CaMg 125.91±6.07 3.42±0.19 19.98±1.57 Embodiment 15 CPAI-10% CaMg 129.37±2.77 3.16±0.10 41.40±2.88

[0130] As can be seen from Table 2, the introduction of a small amount of alkaline earth metal coordination can effectively improve the mechanical properties of the film, among which CPAI-2%Ca has the highest tensile strength (160.21MPa), CPAI-0.5%Ca has the highest elastic modulus (5.0GPa), and CPAI-10%CaMg has the highest elongation at break (41.40%). The above results show that the introduction of a small amount of ions (0.5-2%) can form a multi-coordination form to effectively improve the tensile strength of the film, while the introduction of excessive ions overflows to form a single coordination form to improve the elongation at break of the film.

[0131] The transparent polyamide-imide films CPAI, CPAI-1%Ca, CPAI-1%Mg and CPAI-1%CaMg prepared in Comparative Example 1 and Examples 1-3 were subjected to a bending resistance test. The transparent polyamide-imide films were bent 200,000 times at a bending radius of 0.5 mm, and the morphology of the bending parts was observed. The SEM spectra are shown in FIG. Figure 3 As shown. Among them, Figure 3 Figures a, b, c, and d are SEM images of the bending parts of CPAI, CPAI-1%Ca, CPAI-1%Mg, and CPAI-1%CaMg, respectively. Figure 3 It can be seen that the transparent polyamide-imide film CPAI without alkaline earth metal coordination exhibits clear creases, while the transparent polyamide-imide films CPAI-1%Ca, CPAI-1%Mg and CPAI-1%CaMg with multi-coordination structures have excellent bending resistance.

[0132] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. A method for preparing a bending-resistant transparent polyamide-imide film, characterized in that: include: S1, in an inert atmosphere, dissolving a diamine monomer in a polar organic solvent to obtain a diamine solution; dissolving a dianhydride monomer in the diamine solution to carry out a polymerization reaction to obtain a polyamic acid solution; S2, adding a monovalent alkali metal salt to the polyamic acid solution, and then adding an acyl chloride monomer to carry out a copolymerization reaction to obtain a precursor solution; S3, adding a dehydrating agent and a catalyst to the precursor solution to perform dehydration imidization to obtain a polyamide-imide solution; mixing the polyamide-imide solution with a precipitating agent to perform precipitation to obtain a polyamide-imide solid containing a monovalent alkali metal salt; S4, dissolving the polyamide-imide solid containing a monovalent alkali metal salt in a polar organic solvent, then adding a multivalent alkaline earth metal salt, and stirring evenly; filtering and degassing to obtain a multi-coordinated polyamide-imide solution; S5, coating the multi-coordinated polyamide-imide solution on the surface of the substrate, and curing it by heating to obtain a bend-resistant transparent polyamide-imide film.

2. The preparation method according to claim 1, characterized in that: The diamine monomer includes at least one of the compounds shown in 1-1a to 1-15a:

3. The preparation method according to claim 1, characterized in that: The dianhydride monomer includes at least one of the compounds shown in 1-1b to 1-12b:

4. The preparation method according to claim 1, characterized in that: The acyl chloride monomer includes at least one of the compounds shown in 1-1c to 1-18c:

5. The preparation method according to claim 1, characterized in that: The polar organic solvent includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc); The dehydrating agent is acetic anhydride; The catalyst is pyridine, triethylamine or isoquinoline; The precipitant is deionized water, ethanol or a mixture of deionized water and ethanol.

6. The preparation method according to claim 1, characterized in that: The ratio of the molar number of the diamine monomer to the total molar number of the dianhydride monomer and the acyl chloride monomer is 1:(1-1.03); wherein the molar ratio of the dianhydride monomer to the acyl chloride monomer is 9:1-1:9; The molar ratio of the dehydrating agent to the dianhydride monomer is (2-2.5):1; The molar ratio of the dehydrating agent to the catalyst is 1:(0.5-2).

7. The preparation method according to claim 1, characterized in that: The monovalent alkali metal salt is LiCl; the amount of the monovalent alkali metal salt added is 0.5 to 2.0 wt% of the sum of the amounts of the diamine monomer and the dianhydride monomer; The multivalent alkaline earth metal salt comprises at least one of CaCO3, CaF2, CaSO4, CaCl2, MgCO3, MgF2, MgSO4 or MgCl2; The added amount of the multivalent alkaline earth metal salt is 0.5-10 wt % of the solid mass of the polyamide-imide containing the monovalent alkali metal salt.

8. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the dehydration imidization is 20 to 60° C., and the time is 1 to 24 hours; The precipitation temperature is 10-40°C.

9. The bending-resistant transparent polyamide-imide film prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the bending-resistant transparent polyamide-imide film according to claim 9 in a flexible display device.

Citation Information

Patent Citations

  • Method for preparing polyamide-imide copolymer fibers

    CN105239188A

  • Polyimide high-temperature-resistant lithium battery diaphragm and preparation method thereof

    CN108365151A

  • Preparation method for high-performance polyimide fiber

    CN110184668A

  • Application of metal ion coordination cross-linked polyimide porous membrane

    CN112755822A

  • Polyamide-imide polymers having fluorine-containing linking groups

    US4923960A